Etableringen af "Den Danske Kirke i Amerika" - Holm, Ole (Religionsvidenskabeligt Tidsskrift, 1984)
The subject of the present article is the establishment of “The Danish Church in America”. In the 1860’s, when the emigration from Denmark to the USA began to accelerate, the Danish emigrants who wanted the service of a Lutheran evangelical church still had to turn to non-Danish churches, especially Norwegian and Swedish churches. This problem was recognized in Denmark in the late 1860’s and consequently a committee was formed, which is 1871 began to send out Danish laymen who were then ordained in America for Danish congregations. In 1872 the first Danish ministers in America formed a missionary society, and in 1874 they proclaimed themselves as “The Danish Church in America”. Even if not all of the Danish ministers subscribed to the particular biblical views held by Grundtvig, these biblical views caused vehement opposition to all the new ministers, especially from the more pietistic ministers of the Norwegian churches. In the beginning, ministers of the Grundtvigian observation were able to co-exist in harmony with the more pietistic ministers within the Danish Church, but in 1886 the harmony began to be disrupted by dogmatic dispute. The church was organized in such a way that these disputes could not be brought to an end within the framework of the organisation, and so the church split up in 1894 when the pietistic ministers and congregations left “The Danish Church in America” to form an alternative church.